Henryk Grossmann 2.0: Eine Kritik an Paul Masons Buch „Postkapitalismus: Grundrisse einer kommenden Ökonomie“ - Fuchs, Christian (Z 107)

Een kritiek van Post Kapitalisme, een gids voor de toekomst van Paul Mason - Fuchs, Christian (Marxistische Studies 115)

The Multiple Aspects of Politics and Sustainability in Community Networks. EU Horizon 2020 Project netCommons, Deliverable 2.1 (Version 1, June 2016) - Fuchs, Christian

Screening of mixed-linker CAU-10 MOF materials for humidity sensing by impedance spectroscopy - Weiss, Alexander; Reimer, Nele; Stock, Norbert; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
The sorption properties of mixed-linker CAU-10 type metal organic frameworks (MOFs), [Al(OH)(1,3-BDC-X)n(1,3-BDC-SO3H)m] with 1,3-BDC = 1,3-benzenedicarboxyliate, X = H, NO2 or OH, 0.76 ≤ n ≤ 0.89 and 0.11 ≤ m ≤ 0.24, can be varied by surface modification through variation of the respective linker molecules. It is thus possible to design surface-modified CAU-10 type MOFs with variable affinity and accessibility of the pores for water vapour. When used as a dielectric in a capacitor, the MOF material will change its permittivity depending on the amount of physisorbed water; this is the working principle of capacitive humidity sensors. Three different mixed-linker compounds with CAU-10 structure are compared regarding their water sorption and impedance characteristics. A setup was developed allowing the characterization of the MOF samples under exposure to different relative humidity values in air by impedance spectroscopy. Interpretation of the results by means of standard models shows that the MOFs are qualified for functional layers of capacitive humidity sensors. Since the prepared MOFs are more temperature-stable than many commonly used polymers they offer the potential to build a new generation of high-temperature (up to 350 °C) humidity sensors.

Alltags(schuh)moden der 1930er und 1940er Jahre - Kraft, Kerstin

On the Design, Characterization and Simulation of Hybrid Metal-Composite Interfaces - Kießling, R.; Ihlemann, J.; Pohl, M.; Stommel, M.; Dammann, C.; Mahnken, Rolf; Bobbert, Mathias; Meschut, Gerson; Hirsch, F.; Kästner, M. (Applied Composite Materials)

Critical Learning in Digital Networks - Allmer, Thomas (The Journal of Contemporary Community Education Practice Theory)

Event Driven Modeling and Characterization of the Second Order Voltage Switched Charge Pump PLL - Ali, Ehsan; Hangmann, Christian; Hedayat, Christian; Haddad, Fayrouz; Rahajandraibe, Wenceslas; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

Influence of Traps on the Characteristics of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fabio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Self-aligning integration technique for organic electronics - Meyers, Thorsten; Vidor, Fabio F.; Kaijage, Shubi F.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg K.N.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microstructured Metal Layers in Dye Sensitized Solar Cells - Kleine, Andre; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

ZnO nanoparticle thin-film transistors on flexible substrate using spray-coating technique - Vidor, Fábio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Nanomaterials)
Keywords: General Materials Science; General Chemical Engineering

Oratorium - Höink, Dominik (Handbuch Literatur und Religion)

Formen der Sakralisierung von Komponisten und kreativen Schaffensprozessen im Musikschrifttum - Höink, Dominik (Neues finden – Neues schaffen. Studien und Interviews zu Kreativität in Wissenschaft und Kunst)

Neues finden – Neues schaffen. Studien und Interviews zu Kreativität in Wissenschaft und Kunst
Wissenschaftler und Künstler befinden sich gleichermaßen auf der unentwegten Suche nach „Neuem“. Der Band versammelt Studien zum Thema Kreativität in Kunst und Wissenschaft, deren Spektrum vom kreativen Umgang mit religiösen Diskursformen im Judentum über die Mathematik bis hin zu Medizin, Musik, Recht und Kirchengeschichte reicht. In Interviews im zweiten Teil geben vier Mitglieder der Nordrhein-Westfälischen Akademie Einblick in die Bedeutung von Kreativität für ihr wissenschaftliches oder künstlerisches Schaffen.

Klangbilder. Zur Visualisierung von Musik und musikalischen Verläufen - Höink, Dominik (Visualisierung der Wissenschaft)

Gesang auf der ,imaginierten‘ Bühne. Charakterisierungen der Stimmen von Händel-Solisten in der musikalischen Presse des 19. Jahrhunderts - Höink, Dominik (Händel-Jahrbuch)

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Influence of strong screening effect on the perpendicular polarized linear excitonic absorption spectra of semiconducting carbon nanotubes - Meier, Torsten; Liu, Hong (The European Physical Journal B)
For incident light polarized perpendicular to the tube axis the multi-band semiconductor Bloch equations (MB-SBEs) that involve various screened interband Coulomb interactions (ICIs) are derived. The calculated E 12 peak is very close to the longitudinal excitonic peak E 22. Compared with the previous theoretical peak positions, the blue-shift of the peak in our results is about 0.5 eV. Then, subsequent detailed analyses show that the screening effect on the diagonal ICIs (D-ICIs) plays a key role in this big blue-shift. The valley-degenerate transverse pair excitations holding the same selection rule further enhance the screening effect on D-ICIs. Specially at q = 0 the dielectric function acting on the D-ICIs enhances two times. In our calculation the strong screening effect contributes 90% of the big blue-shift, while the non-diagonal ICIs (ND-ICIs) contribute to 10% of the blue-shift.

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Fundamental studies on a novel die concept for round-point shear-clinching - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (AIP Conference Proceedings)

Ternary quadratic forms over number fields with small class number - Kirschmer, Markus; Lorch, David (Journal of Number Theory)
We enumerate all positive definite ternary quadratic forms over number fields with class number at most 2. This is done by constructing all definite quaternion orders of type number at most 2 over number fields. Finally, we list all definite quaternion orders of ideal class number 1 or 2.
Keywords: Algebra and Number Theory

Indium oxide inverse opal films synthesized by structure replication method - Amrehn, Sabrina; Berghoff, Daniel; Nikitin, Andreas; Reichelt, Matthias; Wu, Xia; Meier, Torsten; Wagner, Thorsten (Photonics and Nanostructures - Fundamentals and Applications)
We present the synthesis of indium oxide (In2O3) inverse opal films with photonic stop bands in the visible range by a structure replication method. Artificial opal films made of poly(methyl methacrylate) (PMMA) spheres are utilized as template. The opal films are deposited via sedimentation facilitated by ultrasonication, and then impregnated by indium nitrate solution, which is thermally converted to In2O3 after drying. The quality of the resulting inverse opal film depends on many parameters; in this study the water content of the indium nitrate/PMMA composite after drying is investigated. Comparison of the reflectance spectra recorded by vis-spectroscopy with simulated data shows a good agreement between the peak position and calculated stop band positions for the inverse opals. This synthesis is less complex and highly efficient compared to most other techniques and is suitable for use in many applications.

Dynamics of dipoles and vortices in nonlinearly coupled three-dimensional field oscillators - Driben, R.; Konotop, V. V.; Malomed, B. A.; Meier, Torsten (Physical Review E)
The dynamics of a pair of harmonic oscillators represented by three-dimensional fields coupled with a repulsive cubic nonlinearity is investigated through direct simulations of the respective field equations and with the help of the finite-mode Galerkin approximation (GA), which represents the two interacting fields by a superposition of 3+3 harmonic-oscillator p-wave eigenfunctions with orbital and magnetic quantum numbers l=1 and m=1, 0, −1. The system can be implemented in binary Bose-Einstein condensates, demonstrating the potential of the atomic condensates to emulate various complex modes predicted by classical field theories. First, the GA very accurately predicts a broadly degenerate set of the system's ground states in the p-wave manifold, in the form of complexes built of a dipole coaxial with another dipole or vortex, as well as complexes built of mutually orthogonal dipoles. Next, pairs of noncoaxial vortices and/or dipoles, including pairs of mutually perpendicular vortices, develop remarkably stable dynamical regimes, which feature periodic exchange of the angular momentum and periodic switching between dipoles and vortices. For a moderately strong nonlinearity, simulations of the coupled-field equations agree very well with results produced by the GA, demonstrating that the dynamics is accurately spanned by the set of six modes limited to l=1.

Photocurrents in semiconductors and semiconductor quantum wells analyzed by k.p-based Bloch equations - Podzimski, Reinold; Duc, Huynh Thanh; Priyadarshi, Shekhar; Schmidt, Christian; Bieler, Mark; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XX)

Gagastyle: zwischen Eindeutigkeit und Entleerung - Schroeter-Wittke, Harald (Pop goes my heart. Religions- und popkulturelle Gespräche im 21. Jahrhundert)

95 Thesen JETZT. Ein Bildungsbuch

Heilige Familie - Theologische Einsichten (Familienfeierabendmahl mit Kind und Kegel) (KID_024) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 35. DEKT Stuttgart 2015)

Bibelarbeit im Zentrum Jugend (Mt 25,1-13) (BAE_006) - Schroeter-Wittke, Harald; Bohnekamp, Hanna; Janus, Richard (Dokumente CD-ROM des 35. DEKT Stuttgart 2015)

Untewrhalt(en) inszenieren - Schroeter-Wittke, Harald (Schriftinszenierungen. Bibelhermeneutische und texttheoretische Zugänge zur Predigt)

Ergötzung und Recreation. Igor Levit spielt die drei großen Variationszyklen von Bach, Beethoven und Rzewski - Schroeter-Wittke, Harald (Praktische Theologie)

Von der Wiege bis zur Bahre - Gesangbuchlieder im Lebenslauf - Schroeter-Wittke, Harald (Klang der Frömmigkeit. Luthers musikalische Erben in Westfalen)

Helmut Simon (1. Januar 1922 bis 26. September 2013) - Schroeter-Wittke, Harald (Kirchliches Jahrbuch 2013 Lieferung 1: Dokumente zum kirchlichen Zeitgeschehen)

Außer Frage: Vom Alten Testament im Religionsunterricht - Schroeter-Wittke, Harald (Junge Kirche)

Kirche en passant. Wieviel Gottesdienst braucht das Land? - Schroeter-Wittke, Harald (Deutsches Pfarrerblatt)

Nina Reusch: Populäre Geschichte im Kaiserreich: Familienzeitschriften als Akteure der deutsche Geschichtskultur 1890-1913, Bielefeld 2015 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Andrea Hofmann: Psalmenrezeption in reformatorischem Liedgut. Entstehung, Gestalt und konfessionelle Eigenarten des Psalmliedes 1523-1650, Leipzig 2015 - Schroeter-Wittke, Harald (Jahrbuch für Westfälische Kirchengeschichte)

Kirchenkritikmusik und Kirchenmusikkritik. Mendelssohn und Wilsing im Dortmunder Konzerthaus - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/103/hsw21.htm)

Musik als Reformation - Reformation als Musik - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/103/hsw20.htm)

Willkommen in Deutschland. Die Toten Hosen spielen "Entartete Musik" - Schroeter-Wittke, Harald (Praktische Theologie)

Meine Lieblings-Weihnachtsmusik - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/103/hsw19.htm)

Wittenberg als Opernort. Zum 150. Geburtstag von Ferruccio Busoni - Schroeter-Wittke, Harald (Praktische Theologie)

Ars Magna. Zum 700. Todestag von Ramon Llull - Schroeter-Wittke, Harald (Praktische Theologie)

Gert Pickel / Yvonne Jaeckel / Alexander Yendell: Der Deutsche Evangelische Kirchentag – Religiöses Bekenntnis, politische Veranstaltung oder einfach nur ein Event? Eine empirische Studie zum Kirchentagsbesuch in Dresden und Hamburg. Baden-Baden 2015 - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

17. Sonntag nach Trinitatis (18.09.2016). Röm 10,9-17(18): Reich für alle – Inklusion mit Paulus - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Michael Jonas: Mikroliturgie. Liturgische Kleinformeln im frühen Christentum, Tübingen 2015 - Schroeter-Wittke, Harald (Liturgie und Kultur)

7. Sonntag nach Trinitatis. Apostelgeschichte 2,41a.42-47: Zauber und Verpflichtung des Anfangs - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien II/2)

Reiseimpressionen zwischen Differenz und Transkulturalität in Wolfgang Büschers "Ein Frühling in Jerusalem" - Müller, Inez (Cadernos de Literatura Comparada)

Herbert Marcuse and Social Media - Fuchs, Christian (Radical Philosophy Review)

Red Scare 2.0: User-Generated Ideology in the Age of Jeremy Corbyn and Social Media - Fuchs, Christian (Journal of Language and Politics)

Le travail digital et l’impérialisme - Fuchs, Christian (Études Marxistes)

Digital Labor and Imperialism - Fuchs, Christian (Monthly Review)

Digitale arbeid en imperialisme - Fuchs, Christian (Marxistische Studies)

Trabajo digital e imperialismo - Fuchs, Christian (Boletín Onteaiken)

Towards Marxian Internet Studies - Fuchs, Christian (Marx in the age of digital capitalism)

Em direção a uma problemática marxista de estudos sobre a internet. Translated by Rafael Grohmann - Fuchs, Christian (Crítica Marxista)

Introduction: Marx is Back: The Importance of Marxist Theory and Research for Critical Communication Studies Today - Fuchs, Christian; Mosco, Vincent (Marx and the Political Economy of the Media. Studies in Critical Social Sciences, Volume 79)

Introduction: Marx is Back: The Importance of Marxist Theory and Research for Critical Communication Studies Today - Fuchs, Christian; Mosco, Vincent (Marx in the Age of Digital Capitalism. Studies in Critical Social Sciences, Volume 80)

Information Ethics in the Age of Digital Labour and the Surveillance-Industrial Complex - Fuchs, Christian (Information Cultures in the Digital Age: A Festschrift in Honor of Rafael Capurro)

Critical Theory - Fuchs, Christian (International Encyclopedia of Political Communication)

What The US Presidential Election Result Tells Us About the Failures Of Big Data Analytics And Neoliberalism As Big Data Capitalism - Fuchs, Christian (The Huffington Post)

User-Generated Ideology on Social Media: A New Study Shows How Users Oppose and Support Jeremy Corbyn on Twitter - Fuchs, Christian (The Huffington Post)

Legal Struggles in the Age of Uber-Capitalism: Are Uber-Drivers Workers or Self-Employed? - Fuchs, Christian (The Huffington Post)

The Facebook/Admiral Scandal Shows The Limits And Dangers Of Big Data Capitalism - Fuchs, Christian (The Huffington Post)

Bosses’ right to snoop on staff emails is an invasion of privacy and ignores the way we work - Fuchs, Christian (New Statesman Online)

Bosses’ right to snoop on staff emails is an invasion of privacy and ignores the way we work - Fuchs, Christian (The Conversation)

Expanding tweets from 140 characters to 10,000? Not nearly radical enough - Fuchs, Christian (The Conversation)

Against Theoretical Thatcherism: A Reply to Nicholas Garnham - Fuchs, Christian (Media, Culture & Societ)

Social Media Research: A Guide to Ethics - Fuchs, Christian; Townsend, Leanne; Wallace, Claire; Jessop, Curtis; Harte, Dave; Perez Vallejos, Elvira; Lepps, Hayley; Holden, Jennifer; Orton Johnston, Kate; Sloan, Luke; Smith, Michael; McGregor, Samantha; et al.

Strategies moving forward: Social movements and progressive governments: A round table discussion - Fuchs, Christian; Smith, R.C.; Gunn, Richard; Asher, Gordon; Cole, Penny (Heathwood Journal of Critical Theory)

Neoliberalism in Britain: From Thatcherism to Cameronism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Selective surface modification in bimodal mesoporous CMK-5 carbon - Weinberger, Christian; Cao, X.; Tiemann, Michael (Journal of Materials Chemistry A)
Ordered, bimodal mesoporous CMK-5 carbon is prepared by using mesoporous SBA-15 silica as a structural mold. The carbon material is chemically modified by oxidative treatment with acidic persulfate solution. This leads to the creation of oxygen-containing functionalities at the pore walls of the carbon (up to 13 wt% oxygen), as confirmed by IR spectroscopy. The oxidative treatment is carried out before removal of the silica mold which ensures that only one of the two distinct modes of mesopores (namely, the intra-tubular pores) is affected; the other mode (inter-tubular pores) is protected from oxidation by the presence of the silica mold. This is proven by water vapor physisorption analysis. The oxidatively treated (intra-tubular) pores are significantly more polar and, hence, better wettable than the untreated (inter-tubular) pores.

Assessment of the density of (meso)porous materials from standard volumetric physisorption data - Weinberger, Christian; Vetter, Simon; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
Characterization and application of (meso)porous materials often require information about the density of the respective samples. For example, the BET surface area is, by definition, normalized to the sample mass; hence, any comparison between samples of different composition needs to take into account their respective densities. Literature data on the densities of porous materials are scarce. Frequently, only bulk-phase densities are available which sometimes differ from those of porous samples, especially for amorphous systems, such as silica or carbon. The apparent density, i.e. the density of the sample excluding the gas-accessible pore volume, is typically determined by helium gas pycnometry utilizing specialized pycnometers. We demonstrate how to obtain the same data from standard N2 physisorption measurements as part of the regular measurement routine. We evaluate the method by reference measurements utilizing a non-porous reference sample (glass rod) to confirm the validity of the method. Then we present results on apparent density measurements of several mesoporous silica materials (MCM-41, MCM-48, SBA-15, KIT-6), mesoporous carbon (CMK-3, -5, -8, -9), and a variety of mesoporous metal oxides obtained by nanocasting.

Tolerance Analysis of Adhesive Bonds in Crash Simulation - Schwarzkopf, G.; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson; Matzenmiller, A. (Procedia CIRP)
The influences of geometrical parameters like adhesive layer thickness and gap-filling on the mechanical properties of adhesively bonded joints are investigated by means of experimental studies with controlled parameter variations. In addition, corresponding simulation models are used to analyse these effects. As a result, the behaviour of joints under variation of manufacturing parameters can be reproduced with high accuracy. Furthermore, the validated simulation models are used to perform sensitivity analysis on a component-like specimen. Based on these studies, tolerance ranges can be specified and robust design optimisation can be carried out.
Keywords: General Medicine

Videoüberwachung als Instrument der Prävention? - Matzner, Tobias (Prävention und Freiheit. Zur Notwendigkeit eines Ethik-Diskurses. Gutachten für den 21. Deutschen Präventionstag am 6./7. Juni 2016 in Magdeburg)

Neither platform nor media company. Popping a filter bubble is not that easy - Matzner, Tobias (Medium.com)

Grasping the ethics and politics of algorithms - Matzner, Tobias (Medium.com)

Personen verwalten oder Personen sein (müssen)? Normen der Privatheit (nicht nur) in der digitalen Kommunikation - Matzner, Tobias (Technisierte Lebenswelt – Über den Prozess der Figuration von Mensch und Technik)

Anonymität - Matzner, Tobias (Handbuch Informations- und Medienethik)

Beyond data as representation: The performativity of Big Data in surveillance - Matzner, Tobias (Surveillance & Society 14 Nr.2)

Do-It-Yourself Data Protection—Empowerment or Burden? - Matzner, Tobias; Masur, Philipp K; Ochs, Carsten; von Pape, Thilo (Data Protection on the Move – Current Developments in ICT and Privacy/Data Protection)

Organic Field-Effect and Nanoparticle Thin-Film Transistors: Static Model - Romero, Adrian; Gonzalez, Jesus; Hilleringmann, Ulrich; Gloesekoetter, Peter (ANALOG 2016; 15. ITG/GMM-Symposium)

Influence of UV irradiation and humidity on a low-cost ZnO nanoparticle TFT for flexible electronics - Vidor, F. F.; Meyers, T.; Hilleringmann, Ulrich; Wirth, G. I. (2015 IEEE 15th International Conference on Nanotechnology (IEEE-NANO))

Improved rf design using precise 3d near-field measurements and near-field to far-field transformations - Hangmann, C; Mager, T; Khan, S; Hedayat, C; Hilleringmann, Ulrich (Smart System Integration-International Conference and Exhibition on Integration Issues of Miniaturized Systems)

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

Geruchswahrnehmung aus der Luft ist meines Wissens nach gestattet.‘ Daten, Drohnen, Drogenfahndung am Beispiel des Cannachoppers - Rolf, Carolin; Shnayien, Marie-Luise (onlinejournal kultur & geschlecht)

„Geruchswahrnehmung aus der Luft ist meines Wissens nach gestattet.“ Daten, Drohnen, Drogenfahndung am Beispiel des Cannachoppers - Rolf, Carolin; Shnayien, Mary (onlinejournal kultur & geschlecht)
Big Data als Technik und Analyseinstrument gesellschaftlicher und ökonomischer Zusammenhänge dringt in weite Bereiche des Alltags vor, obgleich die Folgen dieser neuen Technik noch nicht absehbar sind. In diesem Zusammenhang gewinnen auch Drohnen als unterstützender Teil polizeilicher Ermittlungsverfahren immer mehr an Bedeutung. Eine dieser Drohnen ist der Cannachopper, der, begünstigt durch eine Gesetzeslücke, im April 2009 von der niederländischen Polizei eingesetzt wurde, um illegale Hanfplantagen ausfindig zu machen. Der Artikel kann als Ergänzung zum im Anhang befindlichen Skript des gleichnamigen Radiofeatures gelesen werden und situiert den Cannachopper in einem Gefüge aus Begehren und Wünschen nach Sicherheit, effizienter und kostengünstiger Polizeiarbeit und der Dystopie von totaler Überwachung.

Counterdiabatic driving in spin squeezing and Dicke-state preparation - Meier, Torsten; Opatrný, T.; Saberi, H.; Brion, E.; Mølmer, K. (Physical Review A)
A method is presented to transfer a system of two-level atoms from a spin coherent state to a maximally spin squeezed Dicke state, relevant for quantum metrology and quantum information processing. The initial state is the ground state of an initial linear Hamiltonian that is gradually turned into a final quadratic Hamiltonian whose ground state is the selected Dicke state. We use compensating operators to suppress diabatic transitions to unwanted states that would occur if the change were not slow. We discuss the possibilities of constructing the compensating operators by sequential application of quadratic Hamiltonians available in experiments.

Entanglement classification with matrix product states - Sanz, M.; Egusquiza, I.L.; Candia, R. Di; Saberi, H.; Lamata, L.; Solano, E. (Scientific Reports)
We propose an entanglement classification for symmetric quantum states based on their diagonal matrix-product-state (MPS) representation. The proposed classification, which preserves the stochastic local operation assisted with classical communication (SLOCC) criterion, relates entanglement families to the interaction length of Hamiltonians. In this manner, we establish a connection between entanglement classification and condensed matter models from a quantum information perspective. Moreover, we introduce a scalable nesting property for the proposed entanglement classification, in which the families for N parties carry over to the N + 1 case. Finally, using techniques from algebraic geometry, we prove that the minimal nontrivial interaction length n for any symmetric state is bounded by .

Definite quadratic and hermitian forms with small class number (Habilitation) - Kirschmer, Markus
Die Gitter von Klassenzahl eins oder zwei sind hier verfügbar: http://www.math.rwth-aachen.de/~Markus.Kirschmer/forms/

Ultrafast shift and rectification photocurrents in GaAs quantum wells: Excitation intensity dependence and the importance of band mixing - Duc, Huynh Thanh; Podzimski, Reinold; Priyadarshi, Shekhar; Bieler, Mark; Meier, Torsten (Physical Review B)
A microscopic approach that is based on the multisubband semiconductor Bloch equations formulated in the basis of a 14-band k⋅p model is employed to compute the temporal dynamics of photocurrents in GaAs quantum wells following excitation with femtosecond laser pulses. This approach provides a transparent description of the interband, intersubband, and intraband excitations, fully includes all resonant as well as off-resonant excitations, and treats the light-matter interaction nonperturbatively. For linearly polarized excitations, the photocurrents contain contributions from shift and rectification currents. We numerically compute and analyze these currents generated by excitation with femtosecond laser pulses for [110]- and [111]-oriented GaAs quantum wells. It is shown that the often employed perturbative χ(2) approach breaks down for peak fields larger than about 10 kV/cm, and that nonperturbative effects lead to a reduction of the peak values of the shift and rectification currents and to temporal oscillations that originate from Rabi flopping. In particular, we find a complex oscillatory photon energy dependence of the magnitudes of the shift and rectification currents. Our simulations demonstrate that this dependence is the result of mixing between the heavy- and light-hole valence bands. This is a surprising finding since the band mixing has an even larger influence on the strength of the photocurrents than the absorption coefficient. For [110]-oriented GaAs quantum wells, the calculated photon energy dependence is compared to experimental results, and good agreement is obtained. This validates our theoretical approach.

Precession and nutation dynamics of nonlinearly coupled non-coaxial three-dimensional matter wave vortices - Driben, R.; Konotop, V. V.; Meier, Torsten (Scientific Reports)
Nonlinearity is the driving force for numerous important effects in nature typically showing transitions between different regimes, regular, chaotic or catastrophic behavior. Localized nonlinear modes have been the focus of intense research in areas such as fluid and gas dynamics, photonics, atomic and solid state physics etc. Due to the richness of the behavior of nonlinear systems and due to the severe numerical demands of accurate three-dimensional (3D) numerical simulations presently only little knowledge is available on the dynamics of complex nonlinear modes in 3D. Here, we investigate the dynamics of 3D non-coaxial matter wave vortices that are trapped in a parabolic potential and interact via a repulsive nonlinearity. Our numerical simulations demonstrate the existence of an unexpected and fascinating nonlinear regime that starts immediately when the nonlinearity is switched-on and is characterized by a smooth dynamics representing torque-free precession with nutations. The reported motion is proven to be robust regarding various effects such as the number of particles, dissipation and trap deformations and thus should be observable in suitably designed experiments. Since our theoretical approach, i.e., coupled nonlinear Schrödinger equations, is quite generic, we expect that the obtained novel dynamical behavior should also exist in other nonlinear systems.

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Satisfaction (These 31-35) - Schroeter-Wittke, Harald; Altuchov, Katharina; Armbruster, Ann-Kathrin; Isaak, Vitalij; Janus, Richard; Kling, Malte; Meßollen, Sophie-Katherin (95 Thesen JETZT. Ein Bildungsbuch)

Auf der Suche nach der Identität Europas - Kulturtheologische Thesen - Schroeter-Wittke, Harald ("Und was ich noch sagen wollte..." Festschrift für Wolfgang Kabus zum 80. Geburtstag)

Performative Didaktik - Erinnern und Gestalten - Schroeter-Wittke, Harald; Teckemeyer, Lothar (95 Thesen JETZT. Ein Bildungsbuch)